Production Planning Process Based on the Work Psychology of a Collaborative Workplace with Humans and Robots - Felicita Chromjakova (Machines, 2023)
This study focuses on discerning how economics, as it pertains to work psychology, is lent a new perspective by the compatibility of humans and robots cooperating in the manufacturing sector. The stability of production plans, flexibility of the organizations, and the management of production constitute the basis for such analysis. In this context, initial findings revealed that steady performance by an individual was significantly influenced by a production plan, while the cycle and lead times in place fundamentally affected the behaviour of employees. Observations were made over five years of 200 workers at 100 manufacturers. Times given over to operations and cycles, and throughput, were primarily defined by the technical cycle of the robot. The secondary element of production planning was the employee, whose operator cycle time was informed by that of the robot. The authors set out to deduce which key factors altered the work psychology in situ in manufacturing environments where collaboration occurred between humans and robots. Prerequisites for optimal psychological conditions were identified (the cooperating human, production planner, collaborative workplace, standardized durations of complete tasks, distance between the worker and robot, and data analytics of production flow). Ensuring circumstances are optimal in terms of work psychology is essential to raising productivity and employee performance. Results showed that the operator was directly dependent on the robot in relation to mutual, continuous production flow. A model of production plan stability was devised, informed by the dependence of specific parameters of the planning model. Research was conducted on the reliance of selected parameters, leading to establishment of prerequisites for an optimal work psychology setting in enterprises with such a collaborative structure.